Peran Komunikasi Digital dan Pemberdayaan Komunitas dalam Mengembangkan Ekowisata Berkelanjutan di Kabupaten Belitung - Novianti, Evi; Lazuardina, Annisa; Endayana, Cipta; Pamungkas, Kasno; Bahurekso, Putu Radar; Baitulloh, Taqiy Gusdi; Ajie Nugraha, Katon Sena (Manajemen dan Pariwisata, 2025)
This research analyzes the implementation of tourism policy in Belitung Regency, focusing on the role of digital communication and community empowerment in developing sustainable ecotourism. Employing a qualitative approach with a case study and thematic analysis of official government documents, the study reveals a gap between policy and practice on the ground. The results indicate that sustainable ecotourism is hindered by environmental degradation and pollution, digital communication is not yet optimal due to low digital literacy and fragmented information systems, and community empowerment remains weak with minimal participation and a low entrepreneurship ratio. The study concludes that a strong synergy between digital strategies, community strengthening, and environmental law enforcement is essential to achieve tourism that is not only economically beneficial but also socially and ecologically sustainable.